Does rural Africa have a “youth problem”? - Thurlow, James; Mueller, Valerie (Jeune Afrique Media Group, 2020)
More than 20 million young people, aged 15-24 years, join the workforce in Africa south of the Sahara every year. These young job seekers will need to find work in today’s more competitive global economy, and not everyone thinks they will be successful.